Exploration of the spatial relationship between Xi’an City and its mausoleums from the perspective of time evolution - Liu, Jiaqi; Zhang, Lei; Zhao, Jieyu; Liang, Yuan; Han, Qingxi; Chirwa, Sambirani (Frontiers in Ecology and Evolution, 2023)
The ancient City of Xi’an has a history of more than 7,000 years of civilization, more than 3,100 years of City development, and 1,100 years of capital construction. With the gradual development of urban areas, the number of imperial tombs in Xi’an has reached 72. These mausoleums are large in scale and valuable, yet they are influenced by the rapid development of present urbanization, cities, and mausoleum spaces. The development contradictions between cities and mausoleum spaces progressively become prominent and need to be handled urgently. This article utilizes spacetime as the base scale, GIS spatio-temporal analysis, field research (including aerial photographs of unmanned aerial vehicle (UAV) in the 8 years, 2015–2022), and Pearson analysis to explore the temporal and spatial evolution law between Xi’an’s urban space and the 55 mausoleums dominated by emperors of various dynasties. It was concluded that the nuclear density area distance layout of Xi’an City and the mausoleum is closely related to time and space. Since ancient times, there has always been a relationship between the Spatio-temporal development of Xi’an City and its mausoleums, and the nuclear density area distance layout of the mausoleums is intimately connected to the status and nature of Xi’an City. Currently, mausoleums are part of site protection. However, because of the large space of the mausoleum, the contradiction between the protection and utilization of mausoleum sites and the development of urban space is revealed. This paper hopes to provide urban planners and site protectors with ideas and data support for the Spatio-temporal development of cities and mausoleums and realize the integration of the protection and renewal of mausoleum sites into the path of urban design and planning.